Physical Exercise as a Means of Managing Covid-19; an Insight Review - Tibebu, Awoke; Anjte, Birhanu; Mossu, Yalemwork (Journal of Sports and Exercise Medicine, 2020)
The following document provides important information that everybody know about physical exercise as a means of managing COVID-19. It addresses the health benefits of physical exercise on our body’s immune system, and stress reduction. Already today in the entire world, coronavirus is now the leading causes of morbidity and mortality. It kills thousands of peoples per day worldwide and continues its impact on the governments and the society. Nowadays it is the greatest public health problem in most countries in the world. Since its identification on Jan, 7 by the chines scientists named the pathogen as a novel coronavirus. In the current situation COVID-19 is rapidly spreading worldwide and the number of cases and deaths are rising up speedily. The spread of the virus is a headache to the government in general and the society in particular. The nature of the virus disallowed contacting with one another, working together, meeting, and other activities the majority of government and private business organizations are enforced to discontinue their work. The growing burden of the virus would place millions of jobs at risk an additional 8.8 million people in working poverty around the world. The danger of the disease and loss of employment leads the majority at stress. A chronically stressed person impairs the organism’s ability to mount a strong immune response with a resultant increase in morbidity and mortality.
Keywords: COVID-19; immune system; morbidity; mortality; Physical Exercise; stress